ELEMENTS OF TRADITIONALISM IN LATIN AMERICAN THOUGHT - Davis, Harold (HUMANITAS DIGITAL, 2021)
THE AUTHOR'S EFFORT in this study is to point out the influence of traditional elements in the thought of Latin America. In the most general sense, for this purpose, tradition is equated with the historical meaning of the past. This meaning of the past is often, but not necessarily, the basis of conservative or reactionary political ideologies. Often it is the burden of progressive or even revolutionary thought. In this latter case it may take the form of a utopia drawn from the past, as in some of the eighteenth century French Enlightenment thought. It may be the Indianism of such revolutionaries as Túpac Amaru in Peru; or, as in the writing of Francisco Bilbao of Chile, it may take the form of an essentially evil tradition of Spanish culture and religion-something to be wiped out. The nineteenth century Positivist view Christianity as "superstition" is a similarly revolutionary view of tradition as evil. The UN Economic Commission for Latin America (CEPAL), in one of its reports remarked: "Lo cierto es que las sociedades tradicionales han resultado ser más o menos flexibles y capaces muchas veces de asimilar elementos en extremo racionales en algunos de sus puntos, sin perder por ello su fisionomía."